The JASMONATE ZIM-Domain Gene Family Mediates JA Signaling and Stress Response in Cotton. (3rd October 2017) - Sun, Heng; Chen, Lin; Li, Jianying; Hu, Meiling; Ullah, Abid; He, Xin; Yang, Xiyan; Zhang, Xianlong
Abstract: JASMONATE ZIM-domain (JAZ) family proteins are involved in regulating diverse biological processes in plants. However, their functions have not been well characterized in cotton ( Gossypium spp.). In the present study, 13, 15, 25 and 30 JAZ genes were identified in Gossypium arboretum, Gossypium raimondii, Gossypium barbadense and Gossypium hirsutum, respectively, based on gene homology. Selection and variation analyses showed that the single nucleotide polymorphism (SNP) density of GhJAZ genes in wild species was much higher than that in domesticated species. Expression pattern analysis showed that all the GhJAZ genes are expressed in at least one tissue and respond to one or more stress factors, as well as being induced by some phytohormones. The co-expression network indicated that GhJAZ genes might mediate multiple stress response pathways. Yeast two-hybrid (Y2H) experiments showed extensive interactions among GhJAZ proteins, including homo- and heteromeric interactions. Overexpressing one member of the JAZ gene family, GhJAZ2 (Gh_D06G0810), significantly enhanced sensitivity to salt stress in transgenic cotton. Transcriptome analysis indicated that GhJAZ2 regulates stress responses possibly by participating in α-linolenic acid metabolism and jasmonate signaling, and is involved in the repression of GhMYC2 regulated by GhJAZ2. Our data provide important clues for further elucidating the functions of JAZ genes in cotton.